What makes early internationalising firms grow faster? - Meuric, Pierre-Louis; Favre-Bonté, Véronique (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
Early Internationalising Firms (EIFs) are companies that rapidly expand internationally and achieve a high growth rate over time. Nevertheless, they are impacted by several constraints when it comes to maintaining their trajectory. Research can support these EIFs by promoting a better understanding of their trajectory through the dynamic capabilities approach, which can explain how firms sustain themselves in uncertain and dynamic markets. Thus, in this article that explores 8 EIF cases, we propose a model based on the microfoundations of dynamic capabilities to better understand the international growth of EIFs.